Performance Evaluation of a Melon Seeds Shelling and Separation Machine - Iorpev, T.; Ozumba, I. C.; Onah, R. O.; Adejumo, O. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The scarcity of information on the performance of most machines developed in Nigeria impedes the commercialization of proven indigenous technologies. A newly developed melon seeds shelling and separation machine with the capability to continuously shell conditioned melon seeds and simultaneously separate the seed cotyledons from it shells was evaluated. The machine extracts heat exclusively from the exhaust gases of a gasoline prime mover by heat conduction principle, mildly dry the shelled melon seed mixture before effecting separation of the cotyledons from it shells by aerodynamic and screening principles.  Based on preliminary studies, performance evaluation of the machine was carried out at 900, 1500 and 2100 rpm operating speed and 14, 20 and 26% db moisture content of white edge (Serewe) melon seed variety. The data obtained were analyzed using IBM SPSS statistic software version 25. Results of Analysis of Variance (ANOVA) at P ≤ 0.05 showed that, shelling efficiency and machine capacity varies significantly with the operating speed, moisture content of the seeds, and their interactions; while separation efficiency and seed breakage percentage varies significantly with the operating speed and moisture content of the seeds but not significant with their interactions. An optimal performance of 96% shelling efficiency, 95% separation efficiency, 2.67% seed breakage percentage and 54.23 kg/h machine capacity, was obtained at 2100 rpm operating speed and 20% db seed moisture level. The performance of the machine is satisfactory and therefore recommended for commercialization and adoption by melon seed processors.